Reader comments as press criticism: Implications for the journalistic field. (August 2016) - Craft, Stephanie; Vos, Tim P; David Wolfgang, J
This study examines the actions of readers as press critics and, therefore, as potentially powerful shapers of journalism's cultural capital. An analysis of 2 years' worth of online reader comments on the ombudsman columns of three national news organizations reveals readers' support of – and even nostalgia for – mainstream journalism values such as objectivity, echoing earlier research suggesting the stability of the journalistic field in the face of challenges from new players such as bloggers. But commenters' critiques of journalistic performance also employed social, and not only professional, values, representing a potential challenge to journalist autonomy.